How does monetary policy affect labor demand and labor productivity? - Andrew Benito (IZA World of Labor, 2017)
By supporting aggregate demand, including by easing financial constraints that affect businesses and households, accommodative monetary policy increased employment during the 2008 financial crisis and its aftermath. But, monetary policies that ease financial pressures also reduce necessary restructuring that normally contributes to productivity growth. One reason why productivity growth has been weaker in the aftermath of the crisis is that aggressive monetary policy actions have weakened underlying supply-side performance and labor productivity.
Keywords: E5; J23; 330; monetary policy; labor demand; productivity